2021
DOI: 10.3390/cells10113218
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/AKT/mTOR Signaling Pathway Is Required for JCPyV Infection in Primary Astrocytes

Abstract: Astrocytes are a main target of JC polyomavirus (JCPyV) in the central nervous system (CNS), where the destruction of these cells, along with oligodendrocytes, leads to the fatal disease progressive multifocal leukoencephalopathy (PML). There is no cure currently available for PML, so it is essential to discover antivirals for this aggressive disease. Additionally, the lack of a tractable in vivo models for studying JCPyV infection makes primary cells an accurate alternative for elucidating mechanisms of viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 122 publications
(197 reference statements)
0
9
0
Order By: Relevance
“…However, these data also reveal that GW-5074 could possess a second mechanism of antiviral activity, depending on the cellular context. While JCPyV is known to require virus-induced activation of the MAPK-ERK pathway in the SV40 Large T-Antigen (TAg) transformed SVG-A cell line, the PI3K/AKT/mTOR pathway seems to dominate in primary normal human astrocytes ( 20 22 , 24 27 ). These signaling cascades involve distinct kinases but exhibit significant cross talk via cross-inhibition and cross-activation ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these data also reveal that GW-5074 could possess a second mechanism of antiviral activity, depending on the cellular context. While JCPyV is known to require virus-induced activation of the MAPK-ERK pathway in the SV40 Large T-Antigen (TAg) transformed SVG-A cell line, the PI3K/AKT/mTOR pathway seems to dominate in primary normal human astrocytes ( 20 22 , 24 27 ). These signaling cascades involve distinct kinases but exhibit significant cross talk via cross-inhibition and cross-activation ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…MAPK-ERK inhibitors like U0126 (MEK1/2), PD98059 (MEK1), and sorafenib (C-Raf, receptor tyrosine kinase) inhibit JCPyV infection in SVG-A glial cells ( 21 , 24 ). In contrast, in primary normal human astrocytes, inhibitors of PI3K, AKT, and mTOR, including wortmannin (PI3K), MK2206 (AKT), and rapamycin (mTOR), inhibit JCPyV infection while MAPK-ERK inhibitors like U0126 fail to reduce infection ( 25 ). That GW-5074 potently reduces JCPyV infection in normal human astrocytes therefore suggests that GW-5074 could exert antiviral activity through another compensatory mechanism in this cell type ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the exosomal DEPs in the present study involve multiple cell signaling pathways such as the PI3K/Akt signaling pathway, focal adhesion, extracellular matrix (ECM)—receptor interaction pathway, and are also involved in the regulation of the actin cytoskeleton. The PI3K–Akt signaling pathway is a crucial intracellular signaling pathway that plays a significant role in promoting cell proliferation and metabolism, and certain viruses can exploit this signaling pathway to facilitate their own proliferation [ 48 , 49 ]. Herein, we revealed that 35 exosome-derived DEPs were enriched in the PI3K/Akt signaling pathway, which also represented the highest enrichment in the KEGG analysis of the DEPs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, FOXP3 is upregulated upon human papillomavirus (HPV) infection and may accelerate the cancerous transformation of cervical epithelial cells [ 77 , 78 , 79 ]. JCPyV can activate cellular pathways, including the mitogen-activated protein kinase, extracellular signal-regulated kinase (MAPK/ERK) pathway [ 80 , 81 , 82 , 83 ] and the phosphoinositide 3-kinase/AKT signaling pathway [ 84 , 85 ] that can influence the expression of the FOX TF family, which in turn, may benefit viral transcription, as there are more TFBS in block “c” of the NCCR, isolated from PML patients ( Figure 4 ). Overall, this analysis discovered novel TFBS, specifically related to HOX and FOX TF families that are possibly important in JCPyV replication and disease outcomes.…”
Section: Discussionmentioning
confidence: 99%